Uma solução para a equação da energia cinética turbulenta empregando o método das características - Szinvelski, Charles Rogério Paveglio (2009)
In this study, using the Method of Characteristics and numeric resources, presents a solution to the equation Spectral Density Evolution of Turbulent Kinetic Energy for a Convective Boundary Layer (CBL) in the morning. It presents three models for the evolution of spectral energy density. The first model, based on the assumption of a system of isotropic turbulence, considering only terms of energy transfer inertial and viscous dissipation. The second model adds the term energy production due to the onset of action of the parameter of heat flux on the surface, but consider it a term of energy transfer inertial anisotropy. The third model employs a mixed configuration of the two previous models, assuming thus distinct regions of operation to inertial transfer terms. The results shaped the evolution of the CLC. In this case, the growth of the energy spectrum is modeled by inserting energy in the region of low wave numbers, a region in which the term of anisotropic energy transfer can not transfer the energy introduced by the energy production term. It is observed that in a region of wave number higher there is a stabilization of the parameter variation temporal on the plane characteristics curves (PCC), indicating that the variation of wave number govern the evolution of the energy spectrum. This fact establishes a kind of criterion for stationarity of turbulent flow regimes.